'My Pen is Mightier Than Your Sword…': A Conversation with Reef the Lost Cauze. Issue 2 (3rd April 2017) - Lacey, Sharif 'Reef the Lost Cauze'; Craig, Todd
Abstract: When thinking about elements of hip-hop culture, it becomes important to include cultural brokers and key practitioners in the conversation, so that the culture does not become divorced from the conversations about it. In order to talk about MC/emcee culture, one should include an emcee that is known and respected for the craft. This interview is conducted with veteran Sharif Lacey aka Reef the Lost Cauze.